Tipologi Dan Morfologi Fasade Rumah Tradisional Kampung Ciptagelar - Ramli, Syamsun (University of Merdeka Malang, 2018)
The people of Kampung Ciptagelar are indigenous people who still hold tatali parantikaruhun. The traditional house of Ciptagelar village is rumah panggung. The facade of thetraditional house of Kampung Ciptagelar has developed. The purpose of this research isto describe typology and morphology of traditional house of Kampung Ciptagelar. Thisresearch is descriptive research using qualitative data collection techniques. Primarydata was obtained through observing the field. Secondary references are obtained throughhistorical-comparative research related to the research sites and research topics. Theresults showed that there are two types of roofs, three types of roof terraces, six door types,eight types of windows, two types of walls, and four types of terraces. The researcherclassifies the change of facade of traditional house of kampong into eight groups. Thechange of facade is influenced by social, economic, climate change, and community knowledgeof Kampung Ciptagelar. Tatali paranti karuhun as a cultural factor while maintainingthe red thread of the traditional house of Kampong Ciptagelar.Â DOI: https://doi.org/10.26905/lw.v10i2.2680